2023
DOI: 10.1002/ppp3.10430
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide assessment of microplastic abundance in agricultural soils: The influence of plastic crop covers within the United Kingdom

Samuel J. Cusworth,
William J. Davies,
Martin R. McAinsh
et al.

Abstract: Societal Impact StatementAgricultural soils are substantial receptors of plastic pollution. Plastic crop covers, a facet of agriplastics, may represent an important contribution to microplastic load in agricultural soils. The authors present a nationwide study of agricultural soils in the United Kingdom, comparing microplastic load between sites where plastic crop covers are and are not used for carrot and potato production. Sites where plastic crop covers were used received a higher microplastic load compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The load of surface plastic in the Mediterranean Sea is estimated 23,150 tonnes and therefore is a potential plastic accumulation zone (Chatziparaskeva et al, 2022a). However, studies indicated that the MP abundance in terrestrial ecosystems may be 4-23 times that in the ocean (Li et al, 2021a), and agricultural plastics contribute to MP pollution of agricultural soils (Cusworth et al, 2023). The main sources of MP pollution are presented in Figure 1.…”
Section: Mps In Terrestrial Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…The load of surface plastic in the Mediterranean Sea is estimated 23,150 tonnes and therefore is a potential plastic accumulation zone (Chatziparaskeva et al, 2022a). However, studies indicated that the MP abundance in terrestrial ecosystems may be 4-23 times that in the ocean (Li et al, 2021a), and agricultural plastics contribute to MP pollution of agricultural soils (Cusworth et al, 2023). The main sources of MP pollution are presented in Figure 1.…”
Section: Mps In Terrestrial Systemsmentioning
confidence: 99%
“…MPs can accumulate in the topsoil layer or migrate to deeper soil due to agricultural activities such as irrigation (Ali et al, 2024) and tillage practices (Li et al, 2021b; Lang et al, 2022) and movement to deeper soil layers makes the removal and remediation more difficult (Li et al, 2022b). Therefore, the amount of MPs in agricultural soils and their distribution are affected by the type, amount and history of field amendments, current and previous waste management strategies, and other techniques (Cusworth et al, 2023). Even within the same region, MP pollution can have different levels owing to different cropping characteristics and agricultural practices (Liu et al, 2022b).…”
Section: Mps In Terrestrial Systemsmentioning
confidence: 99%
See 1 more Smart Citation